Nutrient Dynamics of Natural Evergreen Forests in the Eastern Region of Thailand - Parinya Glumphabutr,; San Kaitpraneet,; Chongrak Wachrinrat, (Agriculture and Natural Resources, 2007)
The objective of this study was to investigate the nutrient dynamics of natural evergreen forests in the Eastern Region of Thailand. Study sites included the moist evergreen forest (MEF) and hill evergreen forest (HEF) at Khao Khitchakut National Park, and in the dry evergreen forest (DEF) at Khao Soi Dao Wildlife Sanctuary, Chanthaburi Province. The study period was between January 2001 and December 2002. The results revealed that the above ground biomass production, the rate of annual biomass increment and the rate of litterfall and soil nutrient content were different in the evergreen forests, and therefore affected the nutrient dynamics in each part of the forest. DEF showed the highest rate of nutrient retention in plant and soil systems, followed by MEF and was lowest in HEF. The nutrient dynamics of Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca) and Magnesium (Mg) of these evergreen forests - in terms of uptake rate, return and release rates from litterfall and litter decomposition - were highest in DEF, followed by MEF and lowest in HEF. Furthermore, the nutrient turnover rates in litter on the soil surface were highest in DEF and lowest in HEF. It could be concluded that biomass production, litterfall and soil fertility influenced the nutrient dynamics of the three evergreen forests.